2019
DOI: 10.1016/j.sapharm.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist perceptions of their role and the use of social media and mobile health applications as tools in public health

Abstract: Most CPs, particularly those under 30, were positive about the use of SM and MH apps in PH. Training on the use of such tools among the pharmacy team, and an awareness of the availability of evidence-based apps will ensure their wider adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
(80 reference statements)
1
33
0
Order By: Relevance
“…Robb and Shellenbarger [21] determined the gender are also as an important factor for literacy level. Similar to the present study, it was demonstrated that male pharmacy students had significantly higher score of e-health literacy than female pharmacy students [23]. In another study, it was found that female pharmacy students had higher e-HEALS scores than male pharmacy students [22].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Robb and Shellenbarger [21] determined the gender are also as an important factor for literacy level. Similar to the present study, it was demonstrated that male pharmacy students had significantly higher score of e-health literacy than female pharmacy students [23]. In another study, it was found that female pharmacy students had higher e-HEALS scores than male pharmacy students [22].…”
Section: Discussionsupporting
confidence: 89%
“…In another study, it was found that female pharmacy students had higher e-HEALS scores than male pharmacy students [22]. On the contrary, Crilly et al [23] did not find any significant differences between the gender groups in their study. These discrepancy results may be due to the relatively limited sample and differences in education level in the study sample.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Those working in the primary health sector, such as community pharmacists, form a key part of the public awareness strategy and, in addition, have an important role to play in treating, screening, and providing brief interventions to those who may be at risk of harm [ 14 ]. This aspect of public health has become engrained into the profession of community pharmacy for many years [ 15 ]. There is evidence that when pharmacists take a patient-centered approach, incorporating motivational interviewing and health behavior change models, they are able to engage and support the public better in order to make positive lifestyle choices [ 16 ].…”
Section: Introductionmentioning
confidence: 99%